A Rhetorical Stylistic Analysis of English Political Headlines in Selected Newspapers - Hassan, Sawsan (Al-Adab Journal, 2024)
This study explores the language used in reporting political headlines conducting a rhetorical stylistic analysis. It is based on showing the effect of the rhetorical stylistic relations in news reporting. The aim is to investigate the structure adopted in reporting political news. It argues that the rhetorical stylistic devices are necessary and applicable to non-literary texts, i.e. political headlines to evaluate language use in the representation of non-literary texts. The analysis was carried out on data selected from the British broadsheet The Guardian and the American New York Times newspaper headlines. The data were examined and subjected to a contrastive analysis incorporating rhetorical and stylistic tools to discern how they are united to achieve the main purpose of language use, i.e. to persuade and grasp the reader's attention. It was found that the two newspapers tend to employ sentence structures differently in terms of nucleus and satellite relations demonstrating the significant part in a sentence. Examples of the deviation strategy of foregrounding were primarily established in the New York Times to maintain the reader's attention about the content underlying the different strategy of the two newspapers to report war circumstances. The analysis shows that rhetorical devices and stylistic features are found and closely related in newspaper articles.